"Oko proroka, czyli Hanusz Bystry i jego przygody. Powieść z dawnych czasów" Władysława Łozińskiego. Lektura w kontekście "Tajemnic Paryża" =" The Prophet?s Eye: Hanusz Bystry and His Adventures.Reading" Władysław Łoziński`s Historical Novel in the Context of Eugene Sue`s "The Mysteries of Paris" - Olszewska, Maria Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Assuming that every reading act is not only about ferreting out the literary sense, but also the semioticcontexts, the attempt undertaken in the article is to analyze the historical novel regarding Polishhistory in the seventeenth century, "Oko proroka" (1899) by Władysław Łozinski, in the context ofpopular French contemporary novel, "Tajemnice Paryża" ("Les Mysteres de Paris"; 1842-1843, ed. Polish 1844) by Eugene Sue.
Keywords: Łoziński, Władysław (pisarz; 1843-1913); literatura polska - historia - 19 w.; powieśc polska - 19 w.